Motivation and English Training of Students of Class Viii-A Private Junior High School Santo Thomas 4 Medan, Medan City - North Sumatera - Simanjuntak, Faido M; Simanjuntak, Arthur; Sagala, Farida; Ginting, Mitha Christina; Sagala, Lamria; Simanjuntak, Gracesiela Yosephine; Simanjuntak, Markus Doddy (PT FORMOSA CENDEKIA GLOBAL, 2025)
Learning motivation is defined as the general psychological motivation of students that drives learning activities to achieve goals. Students can succeed in learning if they have learning motivation. Therefore, it is important for students to have high learning motivation in order to study seriously. However, learning motivation works faster if there are external drivers such as empowerment and psychoeducation. This empowerment activity aims to deepen students' understanding of the importance of learning motivation in learning activities and accelerate the development of learning motivation. In addition, the facilitator provides intensive learning support activities for English subjects. The activity was carried out for two days at Santo Tomas 4 Medan Private Middle School and was attended by 21 Class VIII-A students. The contents of the activities carried out included motivating students to stimulate interest in learning English and practicing English vocabulary. This is done so that students understand how to communicate well and correctly and improve their English vocabulary.